Role of the Pseudomonas plecoglossicida fliL gene in immune response of infected hybrid groupers (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Shi, Lian; Zhao, Lingmin; Li, Qi; Huang, Lixing; Qin, Yingxue; Zhuang, Zhixia; Wang, Xiaoru; Huang, Huabin; Zhang, Jiaonan; Zhang, Jiaolin; Yan, Qingpi (Frontiers in Immunology, 2024)
Pseudomonas plecoglossicida, a gram-negative bacterium, is the main pathogen of visceral white-point disease in marine fish, responsible for substantial economic losses in the aquaculture industry. The FliL protein, involved in torque production of the bacterial flagella motor, is essential for the pathogenicity of a variety of bacteria. In the current study, the fliL gene deletion strain (ΔfliL), fliL gene complement strain (C-ΔfliL), and wild-type strain (NZBD9) were compared to explore the influence of the fliL gene on P. plecoglossicida pathogenicity and its role in host immune response. Results showed that fliL gene deletion increased the survival rate (50%) and reduced white spot disease progression in the hybrid groupers. Moreover, compared to the NZBD9 strain, the ΔfliL strain was consistently associated with lower bacterial loads in the grouper spleen, head kidney, liver, and intestine, coupled with reduced tissue damage.Transcriptomic analysis identified 2 238 differentially expressed genes (DEGs) in the spleens of fish infected with the ΔfliL strain compared to the NZBD9 strain. Based on Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, the DEGs were significantly enriched in seven immune system-associated pathways and three signaling molecule and interaction pathways. Upon infection with the ΔfliL strain, the toll-like receptor (TLR) signaling pathway was activated in the hybrid groupers, leading to the activation of transcription factors (NF-κB and AP1) and cytokines.The expression levels of proinflammatory cytokine-related genes IL-1β, IL-12B, and IL-6 and chemokine-related genes CXCL9, CXCL10, and CCL4 were significantly up-regulated. In conclusion, the fliL gene markedly influenced the pathogenicity of P. plecoglossicida infection in the hybrid groupers. Notably, deletion of fliL gene in P. plecoglossicida induced a robust immune response in the groupers, promoting defense against and elimination of pathogens via an inflammatory response involving multiple cytokines.